2019
DOI: 10.13102/sociobiology.v66i1.3366
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Honeybee Colony Losses in Buenos Aires Province, Argentina

Abstract: Honey bees (Apis mellifera) are essential for the ecosystem, so their loss threatens biodiversity and agriculture. Several factors have been proposed as possible causes of both massive losses and Colony Collapse Disorder. In August 2017 episodes of colony losses were registered in General Alvear, Buenos Aires province. The aim of the present study was to find possible causes of these events. The samples were screened for presence of several pathogens and the determination of maternal lineages was also performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…The enzyme acts as an anti-inflammatory by causing hyaluronic acid break down in various tissues, allowing it to enter the tissue. Treatment with hyaluronidase was reported to prevent tumor cells from reaching lymph nodes in T cell lymphoma, and it may have important anticancer effects to stifle tumor growth [ 76 , 77 ]. Recently, Abdel-Monsef and colleagues purified and characterized hyaluronidase enzyme for the first time from Egyptian bee venom homogeneously using DEAE-cellulose and Sephacryl S-300 columns [ 78 , 79 ].…”
Section: Biological Properties Of Bee Venom From a M Lamarckiimentioning
confidence: 99%
“…The enzyme acts as an anti-inflammatory by causing hyaluronic acid break down in various tissues, allowing it to enter the tissue. Treatment with hyaluronidase was reported to prevent tumor cells from reaching lymph nodes in T cell lymphoma, and it may have important anticancer effects to stifle tumor growth [ 76 , 77 ]. Recently, Abdel-Monsef and colleagues purified and characterized hyaluronidase enzyme for the first time from Egyptian bee venom homogeneously using DEAE-cellulose and Sephacryl S-300 columns [ 78 , 79 ].…”
Section: Biological Properties Of Bee Venom From a M Lamarckiimentioning
confidence: 99%
“…The worldwide decline in honey bees has led to a phenomenon called Colony Collapse Disorder (CCD) or Hive Depopulation Syndrome (CDS). Its possible causes have been discussed by several authors around the world, including Argentina (Maggi et al 2013;Requier et al 2018) García et al 2019). Recent research has shown the presence of some of these viruses in some insect species that cohabit the environment of pollinators.…”
Section: A�������mentioning
confidence: 99%
“…La región del Chaco Húmedo se caracteriza por tener en su territorio, un gran porcentaje de poblaciones de abejas africanizadas (Porrini et al 2020). Respecto de la biología de V arroa destructor, sus virosis y su impacto en las abejas melíferas existen antecedentes en otras zonas productoras del país (Maggi et al 2009a(Maggi et al -b, 2010(Maggi et al , 2012a como así también el registro de perdida de colonias de abejas (Garcia et al 2019, Maggi et al 2016, Requier et al 2018.…”
Section: Introductionunclassified